The Impact of Adaptive Physical Education on the Physical and Cognitive Development of Children with Special Needs: A Literature Review - Gatot Jariono; Nurhidayat Nurhidayat; Eko Sudarmanto; Haris Nugroho; Fadilah Umar (Physical Education Theory and Methodology)
Objectives. This study aimed to conduct a literature review to examine the effects of adaptive physical education on the cognitive and physical development of children with special needs (CSN). Adaptive physical education enhances motor skills, physical health, and cognitive function in people with physical, sensory, or intellectual disabilities.